Remember that:
tan(x) = sin(x)/cos(x)
cot(x) = cos(x)/sin(x)
Also recall that:
cos(A+B) = cos(A)*cos(B) - sin(A)*sin(B)
sin(A+B) = cos(A)*sin(B) + sin(A)*cos(B)
So:
cot(A+B) = cos(A+B)/sin(A+B) = cos(A)*cos(B)/(cos(A)*sin(B) + sin(A)*cos(B)) - sin(A)*sin(B)/(cos(A)*sin(B) + sin(A)*cos(B))
and:
tan(A) + tan(B) = sin(A)/cos(A) + sin(B)/cos(B) = ( sin(A)*cos(B) + sin(B)*cos(A) )/( cos(A)*cos(B) ) = a
and:
cot(A) + cot(B) = cos(A)/sin(A) + cos(B)/sin(B) = ( cos(A)*sin(B) + cos(B)*sin(A) )/( sin(A)*sin(B) ) = b
However, you can see that the reciprocals of these two expressions fit nicely into the cot(A+B) expression above, so:
cot(A+B) = cos(A+B)/sin(A+B) = 1/a - 1/b = (b-a)/ab
That is what was to be shown.
2006-10-22 06:42:01
·
answer #1
·
answered by Ted 4
·
1⤊
0⤋
cot(A+B) = (1-tanA.tanB)/(tanA+tanB)
(standard identity, tan(A+B) reciprocal)
= 1/(tanA+tanB)-
(tanA.tanB)/(tanA+tanB)
=1/a -1/((1/tanB)+1/(tanA))
{a given as tanA+tanB}
{dividing tanA.tanB/(tanA+tanB) by tanA.tanB}
=1/a -1/(cotB+cotA){1/tanx=cosx}
=1/a-1/b {given cosB+cosA=b}
=(b-a)/ab as required
i hope that this helps
2006-10-22 13:43:32
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
cot(A+B) = ( cot A cot B - 1 ) / ( cot A + cot B )
= ( cot A cot B - 1 ) / b.
Now show cot A cot B - 1 = (b-a)/a = b/a - 1. That is, show that
cot A cot B = b/a.
b/a = (cot A + cot B) / (tan A + tan B)
= (cot A + cot B) / (1/cot A + 1/cot B)
= (cot A + cot B) / [ ( cot A + cot B ) / (cot A cot B) ]
= cot A cot B.
2006-10-22 14:34:28
·
answer #3
·
answered by James L 5
·
0⤊
0⤋
(b-a)/ab
=cotA+cotB-tanA-tanB/(tanA+tanB)(cotA+cotB)
=1/tanA+1/tanB-tanA-tanB/
(1+tanA/tanB+tanB/tanA+1)
tanA+tanB+-tan^2AtanB-tanAtan^2B
=2tanAtanB+tan^2A+tan^2B
tanA+tanB+tanAtanB(tanA+tanB)
=(tanA+tanB)^2
(tanA+tan)(1+tanAtanB)
=(tanA+tanB)^2
(1+tanAtanB)/(tanA+tanB)
=1/tan(A+B)=cot(A+B)
hence proved
2006-10-22 13:45:57
·
answer #4
·
answered by raj 7
·
0⤊
0⤋